The Politics of Religion and Taxation: Keeping Church and State Separate - Hofmann, Mary Ann (Journal of Management Policy and Practice, 2021)
This paper discusses tax laws and federal court decisions relating to the taxation or exemption of religious non-profit organizations. In a democracy characterized by separation of church and state, what role does the federal government play in regulating the activities and financial transactions of churches and other religious non-profit organizations? What are the federal statutory requirements regarding tax exemption for churches, tax deductibility of donations to churches, and political activity by churches, and are these requirements justified? Does this regulation interfere with the free exercise of religion, or does the federal government violate the establishment clause of the First Amendment by providing inappropriate tax benefits to churches and clergy?